Coinfection of avian hepatitis E virus and different serotypes of fowl adenovirus in chicken flocks in Shaanxi, China - Yuan Zhang; Huanyu Xu; Yinuo Tian; Jirong Tang; Huanqing Lin; Yani Sun; Qin Zhao; En-Min Zhou; Yiyang Chen; Baoyuan Liu (Microbiology Spectrum)
ABSTRACT In poultry, fowl adenovirus (FAdV) and co-infected viruses (such as avian hepatitis E virus, aHEV) are likely to cause decreased egg production, inclusion body hepatitis, and pericardial effusion syndrome. From July to September 2023, eight poultry farms of commercial broilers and commercial layers suffered from increased mortality, decreased egg production, and the presence of hydropericardium-hepatitis syndrome-like gross lesions in Shaanxi province, China. To determine the source of the infection, the viruses of aHEV, FAdV, avian leukosis virus (ALV), Marek’s disease virus (MDV), Newcastle disease virus (NDV), and H9N2 avian influenza virus (AIV) were detected. A total of 240 liver samples were collected from eight farms and detected by molecular etiology methods. The samples were tested positive for FAdV and aHEV and negative for NDV, MDV, ALV, and H9N2 AIV. Phylogenetic analysis based on the hexon loop-1 gene showed that these isolates were clustered into three distinct serotypes: FAdV serotype 4 (FAdV-4), FAdV-8a, and FAdV-8b. The partial ORF2 gene sequences obtained in this study shared the highest identity (76%–97%) with corresponding sequences of other known avian HEV isolates and belonged to gene type 3 avian HEV. Meanwhile, the isolated FAdV in this study could multiply in leghorn male hepatoma (LMH) cells. Overall, the disease may be mainly caused by FAdV and aHEV coinfection on these farms, and this is the first study to discover FAdV-4/8a/8b and avian HEV coinfection in a farm in China.IMPORTANCELast year, eight poultry farms of commercial broilers and commercial layers suffered a serious disease in Shaanxi province, China. After molecular etiological investigation, the disease may be mainly caused by fowl adenovirus (FAdV) (FAdV-4, FAdV-8a, and FAdV-8b) and avian hepatitis E virus (aHEV) (genotype 3 avian HEV) coinfection on these flocks, and this is the first study to find FAdV-4/8a/8b and avian HEV coinfection in a farm. It provides a valuable foundation for the prevention and control of FAdV and avian HEV coinfection in chicken farms.